Valorizing poultry by-products in mealworm production: nutritional and microbiological insights on Tenebrio molitor meal - Oliveira, Thayline Rodrigues de; Lima, Stelio Bezerra Pinheiro; Dourado, Leilane Rocha Barros; Pavan, Bruno Ettore [UNESP]; Silva, Fernando Barros da; Coelho, Neli Lima; Sousa Vaz, João Pedro de; Santos Filha, Maria da Conceição dos; Silva Ribeiro, Kauan da; Santos, Stéphanie Lima dos; Morais, João Vitor Soares; Silva, Luciana Barboza (De Gruyter, 2025)
This study evaluated poultry litter as a sustainable and cost-effective feed substrate for Tenebrio molitor larvae, focusing on its impact on larval development, nutritional composition, and the microbiological safety of the resulting mealworm meal. Diets with varying poultry litter inclusion levels, were tested to assess survival rate, weight gain, development time, and reproductive efficiency. Results demonstrated that poultry litter inclusion up to 50% maintained larval performance comparable to the standard diet, with optimal relative consumption rate (RCR), efficiency of conversion of ingested food (ECI), and relative metabolic rate (RMR). However, at 100% poultry litter inclusion, larval development time increased by 16 days compared to the standard diet and by 11 days compared to the 50% inclusion treatment, indicating nutritional constraints at extreme inclusion levels. Chemical analysis revealed that diets with 40%–85% poultry litter inclusion increased crude protein content while reducing ether extract levels, suggesting improved protein accumulation. Microbiological evaluations confirmed that mealworm meal derived from poultry litter-based diets met safety standards, with no detectable Escherichia coli, Salmonella spp., or other pathogens. These findings highlight poultry litter as a viable and sustainable feed alternative for T. molitor rearing, contributing to waste recycling and circular economy principles. Incorporating up to 50% poultry litter in mealworm diets enhances growth efficiency while ensuring food safety, offering a practical strategy to reduce agricultural waste and produce alternative protein sources. Future research should focus on optimizing substrate formulations and addressing regulatory challenges to enable the commercial adoption of poultry litter in insect farming systems.